2023
DOI: 10.3390/nu15173716
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Disorders Are Important Correlates of Vulnerability in Hospitalized Older Adults

Ganna Kravchenko,
Renata Korycka-Bloch,
Serena Stephenson
et al.

Abstract: With an increasingly aging population worldwide, the concept of multimorbidity has attracted growing interest over recent years, especially in terms of frailty, which leads to progressive multisystem decline and increased adverse clinical outcomes. The relative contribution of multiple disorders to overall frailty index in older populations has not been established so far. This study aimed to assess the association between the vulnerable elders survey-13 (VES-13) score, which is acknowledged to be one of the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
0
0
Order By: Relevance
“…41 It is well-known that vulnerability is associated with cardiometabolic disorders. 42 Kravchenko et al 42 demonstrated that VES-13 score, being a frailty marker, is associated with HF, development of pressure ulcers, and urinary incontinence. In our study, the patients with VES-13≥3 points were characterized by higher NT-proBNP concentration.…”
Section: Discussionmentioning
confidence: 99%
“…41 It is well-known that vulnerability is associated with cardiometabolic disorders. 42 Kravchenko et al 42 demonstrated that VES-13 score, being a frailty marker, is associated with HF, development of pressure ulcers, and urinary incontinence. In our study, the patients with VES-13≥3 points were characterized by higher NT-proBNP concentration.…”
Section: Discussionmentioning
confidence: 99%